2020
DOI: 10.1177/1120672120901698
|View full text |Cite
|
Sign up to set email alerts
|

Effects of topical antiglaucomatous medications on central corneal epithelial thickness by anterior segment optical coherence tomography

Abstract: Purpose: To evaluate the effect of topical antiglaucomatous medications on central corneal epithelial thickness measured by anterior segment optical coherence tomography. Materials and methods: A total of 153 eyes of 153 patients using topical antiglaucomatous medications and 110 eyes of 110 control subjects were enrolled. Glaucoma type, duration of therapy, the number of drugs, and drops/day were noted in the patient group. Patients and control subjects underwent ocular examinations including Schirmer test, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 20 publications
2
12
0
Order By: Relevance
“…Given the increased prevalence of dry eye or ocular surface discomfort in patients with glaucoma, previous studies investigated the effects of IOP-lowering eyedrops on CET and reported smaller CETs in patients with glaucoma [17][18][19]. Since commercially available antiglaucoma eyedrops often contain preservatives, many concerns have been raised regarding the effect of these preservatives on ocular surface health.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Given the increased prevalence of dry eye or ocular surface discomfort in patients with glaucoma, previous studies investigated the effects of IOP-lowering eyedrops on CET and reported smaller CETs in patients with glaucoma [17][18][19]. Since commercially available antiglaucoma eyedrops often contain preservatives, many concerns have been raised regarding the effect of these preservatives on ocular surface health.…”
Section: Discussionmentioning
confidence: 99%
“…When compared to an age-matched control group without glaucoma, the glaucoma group showed statistically significant reduction in CET in all 25 sectors over a 9.0 mm diameter area. Previous studies have reported reduced CETs in patients with glaucoma, but only few studies revealed significant factors affecting the reduction in CET [17][18][19]. Many studies used manual measurements of the central cornea and examined a relatively small number of subjects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Differently, a recent study did not find significant differences in corneal epithelial thickness among patients under different types and durations of treatment, while the only factor influencing corneal epithelial thickness was represented by age [ 77 ]. In a similar study, Dogan et al [ 78 ] reported that there was no significant correlation between corneal thickness and glaucoma type, duration of therapy, number of drugs, and daily drops.…”
Section: Medical Treatmentmentioning
confidence: 94%
“…Discording results in the corneal thickness parameters at AS-OCT o with regard to the number of drugs used [ 76 , 77 , 78 ]…”
Section: Medical Treatmentmentioning
confidence: 99%